Enjoy Poverty: humanitarianism and the testimonial function of images. Issue 1 (2nd January 2017) - Perugini, Nicola; Zucconi, Francesco
Abstract : The overlap between production of humanitarian images and interventions in contexts of natural and man-made catastrophes is growing on a global scale. An increasingly close relationship exists between image production, news production and humanitarian industry. In this article, we argue that this process is transforming the meaning of the social, political and ethical act of bearing witness. We analyse the epistemic and political implications of visual humanitarian testimony through the documentary film Enjoy Poverty (2008), shot in Congo by the Dutch artist Renzo Martens. Examining some of the key scenes of the film, we undertake an analysis of the visual culture of humanitarianism within which the contemporary production of sensational images of strong emotional impact is inscribed and justified. We maintain that rethinking testimonial debt in light of contemporary visual humanitarianism fundamentally means to acknowledge and explore the hierarchical relationship that visual humanitarianism creates between the witnesses, the victims and the spectators. We conclude by arguing that Enjoy Poverty constitutes an attempt to generate a new visual, discursive and political horizon within which one can prevent the transformation of the testimonial relationship into a relationship of power.